THE STRATEGY OF OGAN ILIR DISTRICT’S OFFICE OF POPULATION CONTROL AND FAMILY PLANNING FOR ACTUALIZING THE PROSPEROUS FAMILY - HAK, Nurmala (Nurani, 2020)
This research’s purpose is to know how is the implementation of Family Planning by the office of population control and family planning, women empowerment and child protection, for reaching a prosperous family, balanced population growth, two healthy kids (DAHSAT) in Indralaya Sub-district, OganIlir District, and also to know about the success that has been done by the office of population control and family planning in Indralaya Sub-district, such as come directly to the field (jemput bola) by using dedicated car (mobilkeliling), held a family planning counseling training for health workers and village hall workers, which the goals are to be able to give good service towards family planning acceptor achievement in Indralaya Sub-district, and mainly for achievement of family planning participants that using a contraception device MKJP and NON MKJP. This research used a descriptive research method with qualitative approach, expectedly be able to examine the achieved strategy in implementation of family planning such as by family planning counseling training in Indralaya Sub-district, OganIlir District. Based on the research’s result, the amount of family planning acceptors in year 2017 – 2019 showed a success attempt, this all been done by family planning counselling implementation called communication, information, and education (KB KIE) and also doing some coachings that called by the name of Tribina, Bina Balita, Bina Remaja, Bina Lansia, in Indralaya Sub-district, but in practice it is not maximally deliver good result, because of the limited number of trained counselling workers and the lacks of equipment required, the family planning counselling also has been done in parallel with Integrated Healthcare Center (Posyandu) activities and other related activites.